Analisis dan Pengembangan Strategi Pemasaran Mobil Bekas dengan Pendekatan SWOT dan QSPM (Studi Kasus: CV. X Pekanbaru) - Dermawan, Dedi; Satriardi, Satriardi; Qurthuby, Muhammad; Ardi, Hendri Ali; Denur, Denur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
A competitive used car business is always about how to manage marketing to meet today's and tomorrow's market needs With an inventory of over 15 cars of various brands and types, the company serves diverse consumer segments from economy to premium classes. CV. X Pekanbaru faces serious challenges in its marketing strategy, including high dependence on traditional marketing methods lack of product differentiation, ineffective customer loyalty programs, and suboptimal utilization of customer data. The aim of this research is to analyze and formulate effective marketing strategies for CV.X Pekanbaru in facing competition in the used car industry. The methods used in this study are SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to identify the company's internal and external factors, followed by QSPM (Quantitative Strategic Planning Matrix) to determine strategy priorities.